Diachronic corpus analysis of Russia-Ukrainian conflict - Kalidolda, Y. (KAZGUU Liberal Arts Digest Volume 5. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2023)
This research is aimed to perform diachronic study on mass-media sources related to the conflict of Russia and Ukraine using corpus analysis. The study will conduct the frequency list, collocation, and concordance lines analysis in order to achieve the purpose of discovering and examining variation in language use across diachronic corpus models, identifying and examining the most frequent themes the corpus uses, exploring the lived experiences of the people directly involved in the conflict. The Russia Ukrainian Conflict Corpus (RUCC) contains 88 mass-media articles that are related to this conflict with 95508 number of tokens.
Keywords: Diachronic corpus analysis, Russia-Ukraine conflict, mass media, discursive strategies, frequency list, collocations, concordance lines, thematic analysis, linguistic changes, language patterns, personal experience